Velferdsteknologi – fremtidens helsevesen med eller uten omsorg? - Hauvik, Stine; Vatne, Solfrid (Nordisk tidsskrift for helseforskning, 2020)
Welfare technology - healthcare in the future with or without care? In the future, it will be a challenge to maintain today’s quality of care. Welfare technology may be a solution to reduce the expected care crisis. The public healthcare system is influenced by New Public Management ideals as” what can we afford? rather than “what are the patients` need”. Questions concerning patients’ rights and healthcare providers’ moral obligation seem to be less important. In the discussion Martinsen criticizes that caring has become a secondary term where patients` have less power. To increase the patient’s user involvement, Habermas suggests communicative discourse as a solution to the discrepancy between the public healthcare systems focus on earnings, and the patients’ need for care.